Detrital neodymium isotope composition of IODP Site U1537 - Hallmaier, Moritz; Gutjahr, Marcus; Hemming, Sidney R; Lippold, Jörg; Weber, Michael E; Eisenhauer, Anton (In: Hallmaier, M et al. (2026): Radiogenic isotope compositions of Site U1537 in the Scotia Sea through the last 200,000 years [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.993168 (DOI registration in progress), 2026)
We report radiogenic isotope records of IODP site U1537 in the Scotia Sea through the last 200,000 years. Detrital neodymium (ɛNd) varies between -3.8 and -8.6 (excluding two extremely radiogenic layers influenced by ash, which were excluded for the interpretation). Authigenic and detrital Pb isotope ratios show variations in line with detrital ɛNd. The data shows excursions towards older sediment and water mass sources during terminations, indicating a deglacial Weddell Sea Deep Water Pulse. All isotope measurements were conducted on a Multi-Collector Inductively Coupled Mass Spectrometer (MC-ICP-MS, Thermo Scientific Neptune Plus) at GEOMAR Helmholtz Center for Ocean Research. Smoothed records were fitted to the data with a Loess Bootstrap Model (see dataset in Further Details). For details on sample preparation and measurements consult the main manuscript. The radiogenic isotope datasets are complemented by the > 63 µm sediment weight fraction. For the last 170 ka the reported ages are based on the age model from Lu et al. 2022, older ages follow Weber et al. 2022.
Keywords: Antarctica; detrital; isotopes; Lead isotopes; Neodymium isotopes; Scotia Sea; Southern Ocean; Weddell Sea